2016
DOI: 10.1364/boe.7.000616
|View full text |Cite
|
Sign up to set email alerts
|

Portable handheld diffuse reflectance spectroscopy system for clinical evaluation of skin: a pilot study in psoriasis patients

Abstract: Diffuse reflectance spectroscopy (DRS) has been utilized to study biological tissues for a variety of applications. However, many DRS systems are not designed for handheld use and/or relatively expensive which limit the extensive clinical use of this technique. In this paper, we report a handheld, low-cost DRS system consisting of a light source, optical switch, and a spectrometer, that can precisely quantify the optical properties of tissue samples in the clinical setting. The handheld DRS system was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Previously, we reported the use of spatially resolved DRS in quantifying microvasculature and morphology of psoriasis. Specifically, we observed increased hemoglobin concentration in the dermis and increased mean size of tissue scatterers induced by epidermal hyperplasia on psoriasis patients 15 . In psoriatic skin, the content, such as lipids, and proteins, and structure of stratum corneum and living epidermis are disturbed, and thus the water status as well as skin barrier function are affected 16 18 .…”
Section: Introductionmentioning
confidence: 77%
“…Previously, we reported the use of spatially resolved DRS in quantifying microvasculature and morphology of psoriasis. Specifically, we observed increased hemoglobin concentration in the dermis and increased mean size of tissue scatterers induced by epidermal hyperplasia on psoriasis patients 15 . In psoriatic skin, the content, such as lipids, and proteins, and structure of stratum corneum and living epidermis are disturbed, and thus the water status as well as skin barrier function are affected 16 18 .…”
Section: Introductionmentioning
confidence: 77%
“…32 We found that, in the wavelength range from 500 to 900 nm, while the oxygenated and deoxygenated hemoglobin concentrations of psoriatic skin were distinct from those of normal sites, other skin functional parameters, such as melanin, collagen, and reduced scattering coe cients, did not show statistically signi cant difference between the psoriatic and normal sites. 15 However, using the skin hemoglobin concentration derived from DRS alone is di cult in achieving effective psoriasis diagnosis or monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This observation agrees with what we have reported earlier where the analyzed wavelength range was from 500 to 900 nm. 15 The scattering power law (μ s ' = a*λ -b ) was employed to smooth the reduced scattering spectra in the 940-1,000 nm range, and the tting results are shown as solid lines in Fig. 5.…”
Section: Reduced Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin autofluorescence is attributed to the NADH, FAD and porphyrins molecules in the skin, which makes autofluorescence spectroscopy limited in the number of tissue components detected and specificity of components due to the broad and overlapping spectral features of these molecules [7]. Diffuse reflectance spectroscopy has similarly been used to characterize skin lesions [8] and psoriatic skin [9]. However, this technique is unable to resolve chemical constituents of the skin other than the inherent absorbers hemoglobin, melanin, collagen and bilirubin.…”
Section: Introductionmentioning
confidence: 99%